Monitoring hydraulically-induced fractures in the laboratory using acoustic emissions and the fluorescent method. (April 2018) - Naoi, Makoto; Chen, Youqing; Nishihara, Kengo; Yamamoto, Kazune; Yano, Shunsuke; Watanabe, Shota; Morishige, Yuta; Kawakata, Hironori; Akai, Takashi; Kurosawa, Isao; Ishida, Tsuyoshi
Abstract: We investigated the relation between seismic events and fractures induced by hydraulic fracturing in laboratory experiments under uniaxial loading conditions using granite and shale blocks by monitoring acoustic emissions (AEs). We used a thermosetting acrylic resin mixed with a fluorescent compound as the fracturing fluid and fixed it within the blocks by heating immediately after fracturing. This allowed observation of fluid penetration regions and fracturing patterns on cross-sectional planes under ultraviolet light irradiation. The obtained AE hypocenters and resin penetration regions observed after the fracturing extended on both wings along the loading axis from the fracturing hole for all the samples. This was as expected theoretically, although the AEs were concentrated primarily on only one side for some samples. Patterns of wellbore pressurization histories, AE activities, and resin penetration regions were significantly different between the two rock types. In the experiments using granite samples, wellbore pressure increased linearly until 87.2–97.4% of the peak pressure, followed by a gradual decrease of the rate and sudden drop of pressure (breakdown). AEs started to occur at 49.6–93.2% of the peak pressure, significantly before the breakdown. Resin penetration regions have a width of 10–30 mm and such wide penetration regions resulted in indistinguishable main fractures. For the shale samples, both the nonlinearity of the wellbore pressure–time curve and the AE activity were initiated immediately before breakdown. The number of detected AEs was much smaller than for the granites. Resin in the rock samples showed thin traces with widths of < 1 mm, corresponding to the main fracture. Such dissimilarities between the two rock types likely resulted from differences in their permeability, grain size, and/or mineralogy. We also found aseismic regions that lacked AEs despite evidence of fluid penetration. Although such regions were affected by the fracturing operations, they cannot be revealed by the microseismic observations used in shale gas/oil fields and enhanced geothermal systems. Highlights: Hydrofracking-induced fractures assessed by acoustic emissions and fluorescent method. Fracturing patterns differed considerably between granite and shale samples. Permeability, grain size and/or mineralogy of rocks affect patterns of fractures. Aseismic areas where fluid penetrated without seismic events were clearly identified.